CIVIC-PATRIOTIC EDUCATION IN THE INSTITUTIONS OF THE VILENSKY EDUCATIONAL DISTRICT DURING THE PERIOD OF THE 1870-S – 1917 ACCORDING TO ARCHIVAL DOCUMENTS - Klimko M.K. (Вестник Брянского государственного университета)
The article on the materials of archival documents considers the organization and conduct of events in the Vilensky educational district, which were aimed at educating future defenders and patriots of the Fatherland. The author examined and analyzed the documents of the funds of the National Historical Archive of Belarus. he article notes that the main body of information on this issue is in the 2507 fund of the Vitebsk Directorate of Public Schools, which contains circulars of the Ministry of Education, the trustee of the Vilensky educational district, reports, reports, memos of heads and employees of subordinate educational institutions, reports of inspection inspections. To a lesser extent, the issue of the history of military-patriotic education in educational institutions of the Vilensky educational district is presented in archival affairs covering 1846‒1920. Fund 466 Minsk male gymnasium. The analysis of archival documents made it possible for the author to highlight such basic forms of educational work as conversations before or after worship, lectures, literary and musical evenings, excursions, involvement of students in the opening of monuments and participation in subscriptions for their construction, employment of students, etc. Subjects aimed at the spiritual, moral and physical education of students were introduced into the teaching program in VED institutions.